Evaluation of the Effect of Epilobium angustifolium Aqueous Extract on LNCaP Cell Proliferation in In Vitro and In Vivo Models - Piwowarski, Jakub P.; Bobrowska-Korczak, Barbara; Stanisławska, Iwona; Bielecki, Wojciech; Wrzesien, Robert; Granica, Sebastian; Krupa, Katarzyna; Kiss, Anna K. (Planta Medica, 2017)
Epilobium sp. are commonly used in traditional medicine in the treatment of early stages of benign prostatic hyperplasia and inflammation. It is suggested that a dominating constituent, oenothein B, is responsible for the extracts therapeutic effects. Several bioactivities were established for extracts and oenothein B in various in vitro models, but due to the questionable bioavailability of this dimeric macrocyclic ellagitannin, their significance in the in vivo effects remains unresolved. We have thus focused our attention on a complex comparative investigation of the in vitro and in vivo activities of phytochemically characterized Epilobium angustifolium aqueous extract and oenothein B on prostate cancer cells proliferation.Incubation of different cell lines with E. angustifolium aqueous extract resulted in a significant reduction of proliferation of PZ-HPV-7 and LNCaP cells, which was partly associated with antiandrogenic activity. These effects were fully congruent with oenothein B, examined in parallel. Oral supplementation of rats implanted with LNCaP cells with E. angustifolium aqueous extract 50–200 mg/kg b. w. resulted in a reduction of the occurrence of prostatic adenoma up to 13 %. Oenothein B was not detected in the urine and feces of the E. angustifolium aqueous extract-treated group, however, conjugates of nasutins gut microbiota metabolites of ellagitannins were detected in the urine, while in human volunteers supplemented with Epilobium tea, only urolithin conjugates were present.Despite observing significant and consistent effects in vitro and in vivo, we were unable to point out unequivocally the factors contributing to the observed E. angustifolium aqueous extract activity, facing the problems of an unknown metabolic fate of oenothein B and interspecies differences in E. angustifolium aqueous extract gut microbiota metabolism.
Keywords: Epilobium angustifolium; Onagraceae; oenothein B; prostate cancer; LNCaP; polyphenols metabolites